Analisis Kebijakan Peraturan Walikota Denpasar No 36 Tahun 2018 Tentang Pengurangan Penggunaan Kantong Plastik Sekali Pakai di Kota Denpasar - Farhan, Ikhsan Mughni; Wijaya, Komang Adi Sastra; Yasintha, Putu Nomy (CITIZEN CHARTER, 2023)
Denpasar City has successfully adopted Perwali Denpasar No. 36 of 2018 concerning the decrease of the use of single-use plastic bags since 2019. The usage of plastic bags in Denpasar City was greatly reduced at the start of Perwali Denpasar No. 36 of 2018's implementation, with a drop in modern stores and shopping malls reaching 99.8%, traditional markets reaching 54%, and other commercial stores reaching 80%. However, at this point, due to people's continued use of plastic bags and the government's lax enforcement of restrictions, the policy has deteriorated performance, particularly in the sector of traditional markets and other business stores. The findings of this investigation show that a number of indicators have not been properly met. Keywords: Policy Analysis, Perwali Denpasar No.36 of 2018, Disposable Plastic Bags.